Advancing Point-of-Care Diagnostics in Community Medicine: Evaluation of the Portable ENNOLIFE HCA-TC-200 Analyzer for Hepatorenal and Urinary Testing: Portable Analyzer for Hepatorenal and Urinary Testing - Hu, Ping-Jen; Lai, Yung-Han; Zheng, Cai-Mei; Lin, Hsin-Ting; Wang, Pei-Yu; Yang, Chi-Chen; Fang, Yu-Ann; Chang, Tian-Jong; Lin, Chia-Wei; Lin, Yuh-Feng; Chen, Ming-Yao; Tsai, Hsiao-Chung; et al. (Journal of Medical Biochemistry, 2025)
Background: Accurate and efficient chemical analyzers play a critical role in modern healthcare, particularly in community medicine where early diagnosis and intervention can significantly improve patient outcomes. This study evaluated the diagnostic performance of the novel portable ENNOLIFE HCA-TC-200 analyzer compared to the established Beckman UniCel DxC 880i analyzer, emphasizing its application for point-of-care testing in community settings.Methods: A total of 600 healthy subjects were recruited from Shuang Ho Hospital, Taiwan. The diagnostic accuracy of ENNOLIFE HCA-TC-200 was validated using clinical chemistry assays, specifically assessing hepatic, renal, and urinary biomarkers. The analyzers were compared based on linearity, inter-method agreement, accuracy, and precision.Results: The ENNOLIFE HCA-TC-200 analyzer demonstrated diagnostic accuracy and precision comparable to the Beckman UniCel DxC 880i. High linear correlations (R > 0.97) were found for most hepatic, renal, and urinary markers, with minor deviations observed for albumin (R = 0.92) and urine creatinine (R = 0.80), which remained within clinically acceptable diagnostic ranges. Accuracy assessments showed >97% inter-method agreement across all analytes after excluding extreme outliers, with 100% agreement for hepatic and renal markers.Conclusions: Chronic liver and kidney diseases remain significant public health challenges, especially within community healthcare contexts. The portable ENNOLIFE HCA-TC-200 analyzer effectively addresses these challenges by facilitating rapid, accurate point-of-care diagnostics in community-based settings. This device supports timely disease detection, enhances preventive medicine practices, and promotes personalized healthcare, ultimately contributing to improved community health outcomes.
Keywords: point-of-care diagnostics; portable analyzer; clinical chemistry; hepatorenal diagnostics; urinary biomarkers; community medicine